2012
DOI: 10.1007/s10557-012-6413-1
|View full text |Cite
|
Sign up to set email alerts
|

Metformin in non-Diabetic Patients Presenting with ST Elevation Myocardial Infarction: Rationale and Design of the Glycometabolic Intervention as Adjunct to Primary Percutaneous Intervention in ST Elevation Myocardial Infarction (GIPS)-III Trial

Abstract: BackgroundLeft ventricular dysfunction and the development of heart failure is a frequent and serious complication of myocardial infarction. Recent animal experimental studies suggested that metformin treatment reduces myocardial injury and preserves cardiac function in non-diabetic rats after experimental myocardial infarction. We will study the efficacy of metformin with the aim to preserve left ventricular ejection fraction in non-diabetic patients presenting with ST elevation myocardial infarction (STEMI).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 45 publications
0
43
0
1
Order By: Relevance
“…The GIPS-III trial was a single center, randomized, double blind, placebo-controlled study. The study design, baseline characteristics and primary outcomes have previously been reported [31,32]. In short, patients presenting with STEMI to the University Medical Center Groningen between January 1, 2011, and May 26, 2013 who underwent successful PCI with implantation of at least 1 stent with a diameter of at least 3 mm were eligible for inclusion in the trial.…”
Section: Methodsmentioning
confidence: 99%
“…The GIPS-III trial was a single center, randomized, double blind, placebo-controlled study. The study design, baseline characteristics and primary outcomes have previously been reported [31,32]. In short, patients presenting with STEMI to the University Medical Center Groningen between January 1, 2011, and May 26, 2013 who underwent successful PCI with implantation of at least 1 stent with a diameter of at least 3 mm were eligible for inclusion in the trial.…”
Section: Methodsmentioning
confidence: 99%
“…This study was performed as a substudy of the glycometabolic intervention as adjunct to primary percutaneous intervention in ST elevation myocardial infarction (GIPS)-III trial (clinicaltrials.gov NTC01217307) [1214]. The GIPS-III trial was a prospective, single center, double blind, randomized clinical trial that compared metformin 500 mg twice daily to placebo treatment in 380 non-diabetic patients requiring primary PCI for STEMI.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, several clinical trials are being performed to test this hypothesis. As an example, the Glycometabolic Intervention as adjunct to Primary percutaneous intervention in ST elevation myocardial infarction (GIPS)-III trial is a prospective, single center, double blind, randomized, placebo-controlled trial, which is currently studying the efficacy of metformin with the aim to preserve left ventricular ejection fraction in non-diabetic patients presenting with ST elevation MI (STEMI) [35].…”
Section: Metformin In Patients Following Acute Coronary Syndromementioning
confidence: 99%